Analisis Keamanan Digital Perguruan Tinggi Terhadap Ancaman Siber Generasi Z melalui Metode Defense-In-Depth - Joko Triyanto; Farros Yumna Prabowo; Muhammad Hafizh Nur Hidayat; Ramzy Alfatoni; Ahmad Baehaqi (Jurnal Sains dan Teknologi Informasi, 2026)
Digital transformation in higher education has increased the use of information technology in academic activities, communication, and digital data management. This condition provides various conveniences in the education system; however, it also increases cybersecurity threats toward Generation Z as the primary users of digital technology within universities. This study aims to analyze the cyber defense of higher education institutions in dealing with cyber threats among Generation Z and to identify the most dominant forms of digital threats targeting students. A qualitative approach was adopted through a library research method, examining a range of scholarly journals, academic articles, and literature on cybersecurity, digital literacy, and the digital behavior of Generation Z published within the last three years (2023–2026). The collected data were analyzed descriptively and qualitatively through reduction, classification, interpretation, and synthesis to formulate a layered campus cyber defense model (Defense-in-Depth). The findings indicate that the high intensity of social media usage, low cybersecurity literacy, and oversharing behavior are the main factors contributing to increasing cyber vulnerability among Generation Z. In addition, phishing, personal data theft, social engineering, and cyber radicalism are identified as the most dominant cyber threats within higher education environments. The analysis also reveals that only 40% of students are able to independently recognize phishing threats, while cybersecurity education improves data security knowledge by 8.33 points and technological risk understanding by 10.17 points. Therefore, strengthening cybersecurity literacy, digital education, and the development of adaptive campus cyber defense systems are strategic steps in enhancing digital security in higher education institutions.